As tecnologias da informação e as novas estruturas sociais e econômicas - Machado Filho, Francisco [UNESP] (My University, 2012)
The present study explores the important points to be considered in understanding the characteristics of the network society appointed by Castells and their relations with the state and power. Compares industrial society forged in the eighteenth and nineteenth century with the information society resulting from new information technologies, global connectivity by internet and generating wealth from capital to capital. Its main objective is to highlight the transitory moment of our human relationships and the need to look to the future free from the shackles of the past.

O presente texto trata de pontos importantes a serem analisados na compreensão das características da sociedade em rede apontadas por Castells e suas relações com o Estado e o poder. Compara a sociedade industrial forjada nos século XVIII e XIX com a sociedade da informação advindas das novas tecnologias de informação, da conectividade global por meio da internet e da geração de riquezas do capital pelo capital. Tem como objetivo principal evidenciar o momento transitório de nossas relações humanas e a necessidade de olhar para o futuro livre das amarras do passado.
The information technology and new social and economic structures
Keywords: Convergence; Network society; Communication and power; Convergência; Sociedade em rede; Comunicação e poder